FORMULATION AND EVALUATION OF MOUTH DISSOLVING TABLETS OF OMEPRAZOLE - Jain, Piyush; Gupta, R. N.; Shrivastava, Sandeep (International Journal of Current Pharmaceutical Research, 2016)
Objective: The aim of present study is to formulate mouth dissolving tablet of omeprazole, the drug will be directly absorbed into systemic circulation through buccal mucosa and lead to produce immediate action. Methods: Mouth dissolving tablets of Omeprazole were prepared by wet granulation method. Required quantity of drug and other excipients were weighed and sieved from sieve no.60 for finding homogenous mixer, then a damp mass of mixer was prepared by using distilled water as a solvent, Damp mass was passed through sieve no. 10 and dried the granules at 50 Â°C till moisture remaining less than 2% Results: All the formulated tablets met the pharmacopoeias standard of uniformity of weight, percentage friability, thickness, and drug content. The in vitro disintegration and dispersion studies were also performed, which shows very good bioavailability and drug release profile. Accelerated stability studies were done for four weeks and found that no significant change in drug content and other parameters like hardness and in vitro dispersion time after four weeks even at 50 Â°C. It may be predicted that formulation will be stable for more than one year. Conclusion: The present investigation successfully formulated mouth dissolving tablets of omeprazole with improved drug release profile. The formulation was chosen because it showed good results in terms of cumulative drug release, disintegration time, hardness and friability. The dissolution study of this formulation showed an increase in the cumulative % drug release.